Efficacy of a novel anti-staphylococcal ectolysin P128 in combination with melittin and its versatility in rabbit eye lesion models and as an antimicrobial wound dressing - Low, Shermaine Wan Yu (2019)
With the rise of antimicrobial resistance, there is an urgency for the development of newer antimicrobial agents with novel modes of action. GangaGen Inc. has developed an innovative bacteriophage-derived anti-staphylococcal ectolysin “P128”, which cleaves pentaglycine bridges of bacterial cell membranes. My co-supervisor’s lab has recently developed bee venom-derived antimicrobial melittin peptide derivatives “Mel4” and “Mel5”. Here, we investigated in vitro and in vivo biocompatibility and efficacy of P128 alone and in combination with Mel4/Mel5. We demonstrated that P128 can kill staphylococcal strains with minimum inhibitory concentrations (MIC) 2-8 µg/mL without causing any major toxicity to cultured human cells, even at elevated concentrations (640 µg/mL). Both Mel4 and Mel5 were effective against broad-spectrum pathogenic bacteria, with MIC 8-128 µg/mL. In a rabbit S. aureus keratitis model, P128 displayed therapeutic effects similar to comparator antibiotic Gatifloxacin and did not interfere with wound healing. Moreover, P128-loaded electrospun sodium alginate/polyethylene oxide – polycaprolactone/gelatin core-shell fibers were cytocompatible with cultured mammalian cells and exhibited contact-mediated antimicrobial activity. Furthermore, combinations of P128 with Mel4/Mel5 displayed synergistic effects against a panel of Gram-positive and Gram-negative bacteria. In conclusion, P128 is a versatile antimicrobial that can be combined with Mel4/Mel5 for treating broad-spectrum bacterial infections.